Proactive career orientation and physical mobility preference as predictors of important work attitudes: the moderating role of pay satisfaction. Issue 8 (28th April 2023) - Redondo, Raquel; Sparrow, Paul; Hernández-Lechuga, Gabriela
Abstract: Although protean and boundaryless career orientation have been seen mainly as different yet related constructs, a recent meta-analysis suggests a reconsideration of this career concept structure into a distinction between two independent dimensions of 'proactive career orientation' (including sub-dimensions 'self-directed', 'values driven', and 'boundaryless mindset') and 'physical mobility preferences' (including sub-dimension 'organizational mobility preference'). To examine whether or not this new proposed structure is sustained we analyze the dynamics between the boundaryless career orientation (using with subdimensions 'boundaryless mindset' and 'organizational mobility preference') and attitudinal outcomes of organizational commitment, job satisfaction, turnover intention and pay satisfaction. The results provide empirical validation for the propositions in the meta-analysis, not only regarding career concept structure but also its dynamics. They confirm areas of similarity of 'boundaryless mindset' and protean dynamics but also important differences between these dynamics for employees with a mobility preference. Boundaryless mindset employees are more intrinsically motivated and proactive in developing their career. Those having high organizational mobility preference are more extrinsically motivated and reactive when facing organizational and environmental determinants. The results show that a 'traditional' boundaryless career orientation is a two-sided coin and organizations need to differentially manage the diverse profiles of a boundaryless careers.